Responses of wheat to low luminosity stress and their relations with genetic breeding - Scheeren, Pedro Luiz; Carvalho, Fernando Irajá Félix de; Federizzi, Luiz Carlos (Pesquisa Agropecuaria Brasileira, 1997)
The work was carried out at the Estação Experimental Agronômica of UFRGS, in Eldorado do Sul, Rio Grande do Sul, Brazil, in 1988. The objective was to investigate the influence of low luminosity stress (60% of incident natural light) on six traits in four wheat (IAS 20-Iassul, IAC 5-Maringá, Trigo BR 34 e PF 84431) genotypes and on their corresponding F2 segregating populations (six combinations). When the treatments with and without low luminosity stress were compared, a differentiated behaviour of the parents, as well as of the F2 segregating populations, was observed for all traits assessed. According to this work, evidences indicate that there are greater possibilities of success in improving the main traits involved in wheat yield components if plant selection is made in an environment that favors phenotypic expression of its genetic potencial, that is, in an environment without stress.
Keywords: plant stature; peduncle; tillers; spikelets; grain number; grain weight; Triticum aestivum